Supercritical Fluids: A Promising Technique for Biomass Pretreatment and Fractionation - Escobar, Estephanie Laura Nottar; da Silva, Thiago Alessandre; Pirich, Cleverton Luiz; Corazza, Marcos Lúcio; Pereira Ramos, Luiz (Frontiers in Bioengineering and Biotechnology, 2020)
Lignocellulosic biomasses are primarily composed of cellulose, hemicelluloses and lignin and these biopolymers are bonded together in a heterogeneous matrix that is highly recalcitrant to chemical or biological conversion processes. Thus, an efficient pretreatment technique must be selected and applied to this type of biomass in order to facilitate its utilization in biorefineries. Classical pretreatment methods tend to operate under severe conditions, leading to sugar losses by dehydration and to the release of inhibitory compounds such as furfural (2-furaldehyde), 5-hydroxy-2-methylfurfural (5-HMF), and organic acids. By contrast, supercritical fluids can pretreat lignocellulosic materials under relatively mild pretreatment conditions, resulting in high sugar yields, low production of fermentation inhibitors and high susceptibilities to enzymatic hydrolysis while reducing the consumption of chemicals, including solvents, reagents, and catalysts. This work presents a review of biomass pretreatment technologies, aiming to deliver a state-of-art compilation of methods and results with emphasis on supercritical processes.